Ukrainian Literature in Podlasie: from Dialect to Literary Language (Linguostylistic Studies, 2020)
The article highlights the issue of the Ukrainian authors’ transition from the language of native dialects to the literary language. Having debuted in the spoken tradition discourse, Podlasie writers not only improved the form of their works but also tried to join the Ukrainian literary discourse. They honed their language skills, and not all of them managed to overcome the dialectal influences. The creative work of Ivan Kyryzyuk, Yuri Gavryluk, Yevhenia Zhabinska, Sofia Sachko and other representatives of Northern Podlasie was studied. The authors of the article lay emphasis mainly on the works created in the second half of the twentieth century. The main focus is on new names in the literary process and the problems of their work. The authors try to analyze the features of poetry by authors who, for various reasons, live outside mainland Ukraine.When discussing the phenomenon of the Ukrainian literature in Podlasie, we have to assume that it has witnessed a significant transformation of consciousness, from the Ukrainian-Belarusian borderland dialect (1970s) to its native Ukrainian language version after 1990. It concerns the works of Ivan Kyryzyuk, Yuri Havryliuk, and Yevhenia Zhabinska, in particular. At the same time, for such literary figures as Sofia Sachko or Yustyna Korolko, the classification into Ukrainian or Belarusian literature remains problematic. It would be optimal to state that both poets are part of the niche literary discourse undertaken by the Ukrainian dialect of Bielsk Podlaski.
Keywords: literature,; poetry,; Podlasie,; literary process,; Ukrainian dialect,; literary language,; dialect peculiarities.